Полісько-Дніпровська катастрофа фінального палеоліту з позиції археології - Залізняк, Л.Л. (Археологія, 2008)
Статтю присвячено маловідомій археологам України катастрофічній повені, що прокотилася долиною Дніпра наприкінці палеоліту внаслідок прориву Поліського льодовикового озера. В статье рассмотрена проблема Полесского приледникового озера и его дренажа в долину Днепра в конце плейстоцена. Далеко не новая в геологии концепция периодического прорыва в долину Днепра приледниковых озер Полесской низменности требует анализа с учетом данных археологии. The article describes the problem of Polissyan periglacial lake and its drainage to the Dnipto River valley at the end of Pleistocene. Far from the new in geology conception of recurrent gushes from periglacial lakes in Polissya lowland to the Dnipro River valley needs to be analyzed taking into consideration the archaeological data..